Nobody notices minerva eaudiobook - Kirwan, Wednesday (Recorded Books Inc., 2017)
Wednesday Kirwan has a knack for delighting beginning readers. Meet Minerva, a doggie who's been very naughty today, as her parents would say. She ripped all the stuffing out of dad's comfiest chair, she peeled off wallpaper, she knocked over the milk, and she even poked her poor brother. But despite all her mischief, no one is paying any attention to her. What does a cute little Boston terrier like Minerva have to do to get noticed?